2008
DOI: 10.1111/j.1365-2966.2007.12543.x
|View full text |Cite
|
Sign up to set email alerts
|

On the reconstruction of a magnetosphere of pulsars nearby the light cylinder surface

Abstract: A mechanism of the generation of a toroidal component of large‐scale magnetic field, leading to the reconstruction of the pulsar magnetospheres, is presented. In order to understand twisting of magnetic field lines, we investigate kinematics of a plasma stream co‐rotating in the pulsar magnetosphere. Studying an exact set of equations describing the behaviour of relativistic plasma flows, the increment of the curvature drift instability is derived, and estimated for 1‐s pulsars. It is shown that a new parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Even if the field lines have initially a very small curvature, this curvature might cause a drifting process of plasma, which priduces to the CDI. Osmanov et al (2008a) considered the two-component relativistic plasma in studying the role of the centrifugal acceleration in the curvature drift instability for pulsar magnetospheres. The investigation demonstrated that the growth rate was higher than pulsar Article published by EDP Sciences spin-down rates by many orders of magnitude, which implied that the CDI was highly efficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the field lines have initially a very small curvature, this curvature might cause a drifting process of plasma, which priduces to the CDI. Osmanov et al (2008a) considered the two-component relativistic plasma in studying the role of the centrifugal acceleration in the curvature drift instability for pulsar magnetospheres. The investigation demonstrated that the growth rate was higher than pulsar Article published by EDP Sciences spin-down rates by many orders of magnitude, which implied that the CDI was highly efficient.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the twisting process of magnetic field lines due to the CDI, we apply the method developed by Osmanov et al (2008a) and Osmanov et al (2008b) to AGN winds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the produced electric field should also be considered in Eq. (1) as the next term to be approximated (Osmanov et al 2008).…”
Section: Parametric Curvature Drift Instabilitymentioning
confidence: 99%
“…Then, by taking into account the formula 1 2π e iNϕ dϕ = δ N,0 , preserving only the leading terms of Eq. (19), and also taking into account that the beam components exceed the corresponding plasma terms by many orders of magnitude, one derives the dispersion relation for the CDI (Osmanov et al 2008)…”
Section: Parametric Curvature Drift Instabilitymentioning
confidence: 99%
See 1 more Smart Citation